Understanding sectoral growth cycles and the impact of monetary policy in Turkish manufacturing - Sahinöz, Saygin (OECD Publishing, 2009)
We pursue a two-fold objective in this paper. First, we try to describe comprehensively the behaviour of sectoral growth cycles in Turkish manufacturing by using several statistical measures and to analyse the co-movement between them via correlation and peak-through analysis. One of the remarkable results of this study is the emergence of the "chemicals" and "paper and paper products"sectors as the leading sectors of total manufacturing. Another important result reveals that export-oriented sectors, which have a high correlation with total manufacturing and with each other, appear as the main drivers of total manufacturing. The second objective of this study is to investigate the response of output in Turkish manufacturing industries to monetary policy shocks within the vector autoregressive framework. The results show that all manufacturing sectors respond to a contractionary monetary policy shock with a reduction in absolute output but that the degree of output reduction is not the same in all sectors. The total manufacturing output declines very quickly after the shock, reaching its minimum value within three quarters
Keywords: Economics; Turkey